No association of the dopamine D2 receptor genetic bilocus score (rs1800497/rs1799732) on food addiction and food reinforcement in Chilean adults - Hidalgo Vira, Nicole; Oyarce, Karina; Valladares Vega, Macarena; Goldfield, Gary S.; Guzmán-Gutiérrez, Enrique; Obregón, Ana M. (Frontiers in Behavioral Neuroscience, 2023)
Purpose: Different systems regulate food intake. In the reward system, dopamine (DA) is the main neurotransmitter, and a variety of genetic variants (rs1799732 and rs1800497) are associated with addiction. Addiction is a highly polygenic disease, where each allelic variant adds a small amount of vulnerability. Polymorphisms rs1799732 and rs1800497 are associated with eating behavior and hedonic hunger, but links to food addiction remain unclear. Aim: To evaluate the association between the bilocus profile (rs1799732-rs1800497) of the dopaminergic pathway with food reinforcement and food addiction in Chilean adults. Methods: A cross-sectional study recruited a convenience sample of 97 obese, 25 overweight, and 99 normal-weight adults (18-35 years). Anthropometric measurements were performed by standard procedures and eating behavior was assessed using the: Food Reinforcement Value Questionnaire (FRVQ) and Yale Food Addiction scale (YFAS). The DRD2 genotypes (rs1800497 and rs1799732) were determined by TaqMan assays. A bilocus composite score was calculated. Results: In the normal weight group individuals who were heterozygous for the rs1977932 variant showed higher body weight (p-value 0.01) and abdominal circumference (p-value 0.01) compared to those who were homozygous. When analyzing rs1800497, a significant difference in BMI was observed for the normal weight group (p-value 0.02) where heterozygous showed higher BMI. In the obese group, homozygous A1/A1 showed higher BMI in comparison to A1/A2 and A2/A2 (p-value 0.03). Also, a significant difference in food reinforcement was observed in the rs1800497, where homozygous for the variant (A1A1) show less reinforcement (p-value 0.01). In relation to the bilocus score in the total sample, 11.% showed “very low dopaminergic signal”, 24.4% were “under”, 49.7% showed “intermediate signal”, 12.7% showed “high” and 1.4% showed “very high”. No significant genotypic differences were observed in food reinforcement and food addiction by bilocus score Conclusions: The results indicate that the genetic variants rs1799732 (-141C Ins / Del) and rs1800497 (Taq1A) were associated with anthropometric measurements but not with food addiction or food reinforcement in Chilean university students. These results suggest that other genotypes, such as rs4680 and rs6277, which affect DA signaling capacity through a multilocus composite score, should be studied.